2013
DOI: 10.3390/en6126170
|View full text |Cite
|
Sign up to set email alerts
|

Co-Combustion of Animal Waste in a Commercial Waste-to-Energy BFB Boiler

Abstract: Co-combustion of animal waste, in waste-to-energy boilers, is considered a method to produce both heat and power and to dispose of possibly infected animal wastes. This research conducted full-scale combustion tests to identify the impact of changed fuel composition on a fluidized-bed boiler. The impact was characterized by analyzing the deposit formation rate, deposit composition, ash composition, and emissions. Two combustion tests, denoted the reference case and animal waste case, were performed based on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…Among the predicted products in the marked area (solid triangles and squares) formation of CaSiO 3 (s) is also predicted by equilibrium calculations (Table 3). Despite no formation of Ca−Al− silicates among the equilibrium products, our XRD results 3 confirmed the presence of Ca 2 Al 2 SiO 7 in the bed ash. According to the phase diagram, all predicted compounds were expected to be present as solids in the ref and AW combustion conditions.…”
Section: Phase Diagram Informationsupporting
confidence: 90%
See 2 more Smart Citations
“…Among the predicted products in the marked area (solid triangles and squares) formation of CaSiO 3 (s) is also predicted by equilibrium calculations (Table 3). Despite no formation of Ca−Al− silicates among the equilibrium products, our XRD results 3 confirmed the presence of Ca 2 Al 2 SiO 7 in the bed ash. According to the phase diagram, all predicted compounds were expected to be present as solids in the ref and AW combustion conditions.…”
Section: Phase Diagram Informationsupporting
confidence: 90%
“…This finding is confirmed in chemical fractionation analysis as well (Figure 6), where elevated levels of Ca and P are attributed to the presence of acid-soluble compounds. 3 It should be noted that according to previous research, 15,17,18 the additional P in the ashes of the AW case is attributed to two main sources in the animal waste: hard and soft tissue. Hard tissue refers to crushed bones that contain Ca 10 (PO 4 ) 6 (OH) 2 and β- Ca 3 (PO 4 ) 2 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, in the last decade, a great deal of research has been conducted to burn waste biomass in various boilers, for example, for the analysis of the combustion tests in a commercial residential wood pellet boiler with a pure SCG pellet, a blended pellet (50% SCG and 50% sawdust) and a pure pine wood pellet [13], for the fuel and combustion test in a small boiler (6.5 kW) with SCG [2], the combustion tests of wood pellet on a fixed bed reactor with various conditions [14], and the combustion test of a fluidized bed boiler with fuel of a normal sold waste and mixing with animal wastes [15]. The combustion of straw, olives, tomatoes, cocoa beans, etc., achieved a relatively high boiler efficiency, but the problem is the emerging ash with a relatively low melting point.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the particle size of the wood pellet and water content are major parameters on combustion and heat transfer. Moradian et al [24] performed the combustion test on a fluidized bed boiler with fuel of a normal solid waste and compared it to mixing with animal wastes. They found that solid waste comprised of 20-30% animal waste reduced the bed temperature by 70-100 • C and suppressed the deposition growth rate.…”
Section: Introductionmentioning
confidence: 99%